Comparing everolimus-based immunosuppression with reduction or withdrawal of calcineurin inhibitor reduction from 6 months after heart transplantation: The randomized MANDELA study - Barten, Markus Johannes; Hirt, Stephan; Dösch, Andreas (American journal of transplantation, 2019)
In the 12-month, open-label MANDELA study, patients were randomized at month 6 after heart transplantation to (1) convert to calcineurin inhibitor (CNI)-free immunosuppression with everolimus (EVR), mycophenolic acid and steroids (CNI-free, n = 71), or to (2) continue reduced-exposure CNI, with EVR and steroids (EVR/redCNI, n = 74). Tacrolimus was administered in 48.8% of EVR/redCNI patients and 52.6% of CNI-free patients at randomization. Both strategies improved and stabilized renal function based on the primary endpoint (estimated GFR at month 18 posttransplant postrandomization) with superiority of the CNI-free group vs EVR/redCNI: mean 64.1 mL/min/1.73 m2 vs 52.9 mL/min/1.73 m2; difference + 11.3 mL/min/1.73 m2 (P < .001). By month 18, estimated GFR had increased by ≥ 10 mL/min/1.73 m2 in 31.8% and 55.2% of EVR/redCNI and CNI-free patients, respectively, and by ≥ 25 mL/min/1.73 m2 in 4.5% and 20.9%. Rates of biopsy-proven acute rejection (BPAR) were 6.8% and 21.1%; all cases were without hemodynamic compromise. BPAR was less frequent with EVR/redCNI vs the CNI-free regimen (P = .015); 6 of 15 episodes in CNI-free patients occurred with EVR concentration < 5 ng/mL. Rates of adverse events and associated discontinuations were comparable. EVR/redCNI from month 6 achieved stable renal function with infrequent BPAR. One-year renal function can be improved by early conversion to EVR-based CNI-free therapy but requires close EVR monitoring. Clinical trials registry: ClinicalTrials.gov NCT00862979.